Original papersEvaluation of the usefulness of coronary catheters and 4 Fr insertion sets for transradial access coronarography in comparison with catheters and 5 Fr sets - Chodór, Piotr; Morawski, Stanisław; Sulik-Gajda, Sylwia; Ramus, Nela; Kowalczyk, Jacek; Honisz, Grzegorz; Wilczek, Krzysztof; Średniawa, Beata; Kalarus, Zbigniew (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Introduction: Application of transradial arterial access during coronarography, besides pain, means faster patient mobilization and fewer complications. During those procedures, vascular sheaths and 5/6 Fr catheters, and lately 4 Fr catheters, are used. Aim: To assess the usefulness of 4 Fr catheters and sheaths in comparison to 5 Fr in diagnostic coronarography. Material and methods : In the period from 5.12.2010 to 27.02.2012, a group of patients who had coronarography with a 4 Fr catheter (n = 20) and a 5 Fr catheter (n = 20) were studied. Technical issues and potential problems related to the use of each catheter were analyzed. Morphology, biochemical parameters, and local complications were analyzed. The assessment included pain intensification during catheter removal and insertion in the VAS/numerical (0–10)/verbal scales and the quality of image obtained during the coronarography. Results: All the angiograms obtained during all the interventions were of diagnostic value and in invasive cardiologists’ opinions, they did not differ statistically in clarity. Moreover, there were no statistically significant differences in radiation/fluoroscopy time, amount of contrast medium, or morphological and biochemical parameters. The size of hematomas in the 4 Fr group was 17.55 ±14.6 cm 2 , and in the 5 Fr group 31.07 ±32.11 cm 2 , p = 0.12. The average intensity of pain felt during the intervention/at the time of its removal and insertion in the numerical scale was in the 4 Fr group 0.65 ±0.93/0.55 ±0.94 and in the 5 Fr group 1.88 ±1.64/1.42 ±1.61, p < 0.05. Conclusions : Application of 4 Fr catheters allows one to perform a diagnostic procedure with a small number of local and hemorrhagic complications comparable with 5 Fr catheters. Due to reduced pain, it is appropriate to continue studies with the use of 4 Fr catheters and sheaths.